Implementasi Strategi Pengembangan Usaha Bagan Apung Rakit Skala Kecil Untuk Meningkatkan Pendapatan Nelayan Kecil di Ohoi Namar, Kabupaten Maluku Tenggara - Simon Marsholl Picaulima (Universitas Tanjungpura, 2023)
Catching efforts in the small-scale lift net raft floating business in Ohoi Namar, Southeast Maluku Regency, continues to increase in quantity, information obtained in the field shows that there was an additional 5 units of small-scale lift nets raft floating fleets from 2012 to 2022, but the increase in fishing effort has not been able to increase the income of small fishermen, these problems are generally influenced by internal and external factors. Therefore, the right step that needs to be taken to increase income is to provide counseling and implement a strategy for developing a small-scale floating raft business using lecture and discussion methods followed by evaluation and monitoring of these small fishing businesses. The strategy for developing the lift net raft floating business can be conveyed well and based on the evaluation results of the participants it shows that the material presented can be well understood, this is evidenced by the number of participants included in the sufficient category of 20 people with a value range of 76-100, the sufficient category is 5 people with the value range is 60-75 and no one is in the less category with a value range <60. Monitoring of the fishing business is not carried out because the fishing business is not operating and it is the west season. however, to further increase income, additional capital is needed and assistance from academics, bureaucracy and private/BUMN.